Agency Costs and Scarce Resources: Influences on Brazilian Franchising - Eugenio Jose Silva Bitti (BBR - Brazilian Business Review, 2019)
This paper revisits a traditional issue in literature on franchising: the contractual mix (i.e., the proportion between franchised and company-owned stores). We analyze 270 Brazilian chains to better understand the Brazilian scenario. We stress the dynamics of this proportion over time considering the perspective of monitoring costs and the difficulty of access to resources as possible explanations. Considering the moment of the Brazilian economy, it is pertinent and opportune to investigate the behavior of the chains in times of turbulence. Panel data covering the 2011-2016 period was analyzed through econometric tools. The results corroborate aspects related to monitoring and incentives advocated by the agency theory, that is: costs of monitoring in elevation due to the geographic dispersion induce a greater proportion of franchised stores. In addition, the concept of dispersion is extended to capture socioeconomic aspects of the different regions occupied by the chains. Effects related to restriction to scarce resources are also noted, but in a less unambiguous way.